Bases para a compreensão do potencial de carbono azul em manguezais brasileiros: um experimento e uma revisão bibliográfica - Beloto, Natália (2024)
Mangroves store large amounts of carbon in their compartments (trees, leaves, downed woods, roots and soils), but especially in soils (>70%). However, the conditions that promote these environments as one of the largest carbon stores in the world are not fully understood. Because of its characteristics salty and flooded, the manner that organic matter (OM) decomposition occurs can be one of factors that enhance carbon storage and permanence in the soil, but others several factors have been investigated to comprehend this high carbon potential. We investigated decomposition of organic matter in soil (DMOS) in north and northeast mangroves and made a systematic bibliographic review to identify gaps in information about carbon in mangrove compartments. To access DMOS, Tea bag index (TBI) methodology was tested, then tea bags were buried in amazon and semi-arid mangroves and later (~25 and 90 days) collected for analysis. And PRISMA methodology was applied to proceed a systematic review, in which articles were searched for and screened using three scientific databases. Results presented higher percentages of DMOS in northern region than northeast. Stabilisation factor (S) and decomposition taxes (k) differed between regions, possibly because of distinct characteristics and environmental conditions of amazon compared to semi-arid mangroves. In addition, systematic review revealed differences between carbon stocks in the mangrove compartments of Brazilian's regions (north, northeast and southeast), and although states such as Amapá and Maranhão have extensive mangrove area in its territories, surprising there are no data available on carbon stocks for these states. Based on results of review, an average of 443 Mg C ha-1 of total ecosystem carbon (TECS) was attributed to Brazilian mangroves, and ~0.44 PgC for the entire national territory. Finally, results reiterate the importance of mangrove as efficient carbon sinks, highlighting the necessity to evaluate all mangrove characteristics to better understand carbon storage processes. This work is related to the UN Sustainable Development Goals 13 (Action against Global Climate Change) and 14 (Life in Water).